A study on depression, anxiety and stress among first year students at school of medical sciences, school of dental sciences and school of health sciences, Health Campus Universiti Sains Malaysia, Kelantan - Shahar, Sharifah Nor Hida Yah Syed (Universiti Sains Malaysia, 2015)
Changes of a students from school environments to university environments could cause a psychological, academic and social shock to them, since this educational system has big different, make them to face variety of demands such as learned in a new method, have heavy workload, living away from families, the relations between students, and so on. This will make them more vulnerable to emotional disturbances such as depression, anxiety and stress. The objectives of this study are to identify the prevalence of depression, anxiety and stress and the main sources of stressor among first year students at School of Medical Sciences, School of Dental Sciences and School of Health Sciences Health Campus Universiti Sains Malaysia, Kelantan. Depression, Anxiety and Stress Scale (DASS-42) were used in order to meet the objectives and about 164 of first year students were involved in this study. The overall prevalence of depression, anxiety and stress was 24.3%, 62.8% and 40.2% respectively. Between genders, the male students had significant association with depression while, School of Health Sciences also found had significantly association with depression. Regarding the sources of stressors, the top ten stressors decided by the students were mainly interpersonal and intrapersonal factors. Factors including change in living environment, increased workload, anticipation of graduation and change in social activities can be considered as source of stressors that possible caused for depression, anxiety and stress while, the most stressors was change in living environment.